Program Kawasan Ramah Ibu Hamil sebagai Upaya Preventif untuk Mengurangi Kecenderungan Psychological Distress - Astriani, Defi (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2024)
Pregnant women are vulnerable to problems that can create high stress and have a negative impact on their emotions. The desire to be a good and perfect mother can cause pregnant women to face a number of problems or what is called psychological distress. Therefore, immediate solutions are needed to reduce high levels of stress which cause psychological pressure and play an important role in preventive efforts in reducing various types of psychological disorders. This service program aims to provide more knowledge related to the problems of pregnant women and be able to provide mutual support among the surrounding community so that serious problems are minimized and the community can become a good forum for its citizens to exchange ideas and share stories. This preventive service program is provided through providing psychoeducation, discussion, relaxation training, role play and evaluation. The results of the service program show that there is a significant difference in the average psychological distress score between before and after the intervention with a value of p = 0.004 (p < 0.05). The post-test average score of 23.1 is lower than the pre-test average score of 38.3. This means that the intervention provided can reduce the level of psychological distress in pregnant women.